(untitled) (NAU Journal of Technology and Vocational Education, 2024)
This study appraised the safety practices of industries in the three out of the six major areas of Technical Education, which span across building, mechanical, and electrical technology industries. Two research questions and two null hypotheses, tested at 0.05 level of significance guided the study. A 15-item questionnaire, meant to ascertain the safety practices in the workplace was administered to 30 factory workers in the three industries in three areas of technical education. The instrument which was validated by experts, yielded a reliability coefficient of 0.87. Mean was used to analyze data to answer the research questions, while Analysis of Variance (ANOVA) was employed to test the hypotheses. Findings showed that the prevalence of accident in industries is not because of absence of safety equipment, but a combination of careless attitude of workers, and employers’ failure to enforce compliance to safety rules. The study also revealed that safety practices in an industry does not depend on the type of work it engages in. The findings have implications for technical education practitioners. Amongst others, it was recommended that industries should provide adequate measures to safeguard the health of workers.